2016
DOI: 10.1177/0883073816630088
|View full text |Cite
|
Sign up to set email alerts
|

Is Celiac Disease an Etiological Factor in Children With Migraine?

Abstract: To determine the prevalence of celiac disease in children and adolescents with migraine, the authors investigated serum levels of tissue transglutaminase antibody immunoglobulin A and total immunoglobulin A from 81 children with migraine and in a healthy control group of 176 children. Study participants who were positive for tissue transglutaminase immunoglobulin A antibodies underwent a duodenal biopsy. Two patients in the migraine group (2.5%) and 1 in the control group (0.57%) tested positive for serum tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Information about prevalence of GS in children with headache (all reporting migraine), was available through three case-controlled studies [ 41 , 47 , 48 ]. As shown in Figure 6 , the pooled mean prevalence of GS in children with idiopathic migraine is 6.2% (95% CI 2.6–14.1%).…”
Section: Resultsmentioning
confidence: 99%
“…Information about prevalence of GS in children with headache (all reporting migraine), was available through three case-controlled studies [ 41 , 47 , 48 ]. As shown in Figure 6 , the pooled mean prevalence of GS in children with idiopathic migraine is 6.2% (95% CI 2.6–14.1%).…”
Section: Resultsmentioning
confidence: 99%
“…Faced with a higher prevalence of migraine in CD patients compared to controls, current evidence does not clearly support the adoption of a routine search for IgA antitransglutamase antibodies within the diagnostic approach for patients with migraine [ 278 , 279 ]. Only one cross-sectional study has reported a higher prevalence of positive tissue transglutaminase IgA (tTGA) antibodies in a group of paediatric migraine patients (5.5%), compared to age- and sex-matched controls (0.6%).…”
Section: Headache and Immuno-mediated Gastrointestinal Disordersmentioning
confidence: 99%
“…The other study, conducted by Balci et al, reported similar results, with 2 among the 81 patients having migraine exhibiting positivity for anti-tTG antibodies compared to 1 among the 176 controls (p = ns). In the same study, the duodenal biopsy was negative in all the subjects, who were then considered 'potential celiacs' [24].…”
Section: Prevalence Of Celiac Disease In Both Adult and Pediatric Patients With Migrainementioning
confidence: 99%
“…In a study by Lahat et al, it was observed that the anti-Endomysial antibodies were negative in all 41 children with migraine headache (1-16 years of age) [22]. Five related case-control studies are available in the literature [23][24][25][26][27], two of which, both conducted with the Turkish population, reported negative findings [23,24]. In one of these studies, no difference was observed in the positivity of anti-tTG between the migraine patients and the healthy controls (2% in both; 2/100 versus 30/1500, respectively) [23].…”
Section: Prevalence Of Celiac Disease In Both Adult and Pediatric Patients With Migrainementioning
confidence: 99%